Association between social support and viral load in adults on highly active antiretroviral therapy – Witbank, South Africa - Temnewo M. Habte; Charles Bondo; Lushiku Nkombua (South African Family Practice)
Background: There are significant number of patients who are on highly active antiretroviral therapy (HAART) not virally suppressed, which is a huge clinical challenge. Social support as a non-pharmacological factor, which may influence the viral suppression, is less studied and has equivocal results. The aim of this study was to investigate the association between social support and viral load (VL) in adults on HAART.